The Impact of Regular Foot Exercise on Blood Glucose Reduction in Type II Diabetes Patients: A Case Study - Trisna, Efa; Jamila, Jamila; Setiawati, Setiawati; Hartati, Sri; Wibowo, Wahyu Dwi Ari; Putri, Hadeci Lovenda; Syifa, Faidana Yaumil (Universitas Malahayati, 2025)
ABSTRACT Elevated blood glucose levels in type II diabetes mellitus (DM) can lead to chronic complications, including cardiovascular, renal, and neurological disorders. The prevalence of type II DM in Indonesia continues to increase, particularly among older adults, many of whom face challenges in adhering to treatment. Non-pharmacological therapies, such as foot exercise, are considered beneficial in improving glycemic control and enhancing lower limb circulation. To describe the outcomes of implementing foot exercise as a nursing intervention for older adults with type II DM who experience unstable blood glucose levels in the working area of Panjang Public Health Center, Bandar Lampung. This case study involved two older adults diagnosed with type II DM. The intervention included foot exercise therapy conducted three times a week over six sessions, each lasting 15–20 minutes. The approach utilized family-centered nursing care with education and monitoring of blood glucose before and after each session. Subject I showed a reduction in random blood glucose levels from 232 mg/dl to 182 mg/dl after three sessions. Subject II experienced a decrease from 248 mg/dl to 189 mg/dl. The variation in reduction was influenced by factors such as medication adherence, presence of comorbidities (e.g., hypertension and diabetic neuropathy), and family involvement. Foot exercise therapy can effectively reduce blood glucose levels in older adults with type II DM. This intervention is recommended as a complementary nursing strategy in diabetes management. Keywords: Foot Exercise, Hyperglycemia, Older Adults, Non-Pharmacological Therapy, Type II Diabetes Mellitus.